The Relationship Between Conflict Risk of Sumatran Tiger (Panthera tigris sumatrae) and Vegetation Density in The Leuser Ecosystem Area of South Aceh District - Istafan Najmi; Wira Dharma; Saida Rasnovi (Elkawnie, 2025)
Abstract: Sumatran tigers (Panthera tigris sumatrae) in the Leuser Ecosystem of South Aceh rely heavily on dense and diverse vegetation for food and protection. However, vegetation degradation due to deforestation and land conversion has pushed tigers out of their natural habitat, increasing the risk of conflict with humans which threatens the species' survival. This study aims to analyze the relationship between tiger conflict risk and vegetation density using the Normalized Difference Vegetation Index (NDVI). The research method combines a Participatory Rural Appraisal (PRA) approach and satellite image-based spatial analysis (Landsat 8/9 or Sentinel) to calculate NDVI, while conflict data was collected through SMART patrols in 13 villages and mapped with ArcGIS. The results show that the Sumatran tiger conflict risk is spatially distributed with a significant level of variation in the study area. High risk dominates with a percentage of 61.5%, mainly concentrated in five sub-districts: Trumon Tengah, Trumon Timur, Tapak Tuan, Kluet Tengah, and Meukek. Meanwhile, moderate risk (23.1%) was identified in Bakongan Timur and Trumon Tengah, and low risk (15.4%) was only found in Bakongan Timur. There is a striking pattern between vegetation density and conflict frequency, with low vegetation areas such as Bakongan Timur (7 cases) and Trumon Tengah (6 cases) recording the highest number of conflicts. In contrast, sub-districts with high vegetation cover such as Meukek, Tapaktuan, and Central Kluet recorded only one case each. These findings strongly indicate that habitat degradation, indicated by low NDVI values, is the main factor driving the increase in negative tiger-human interactions in the region. Abstrak: Harimau Sumatera (Panthera tigris sumatrae) di Kawasan Ekosistem Leuser, Aceh Selatan, sangat bergantung pada vegetasi yang lebat dan beragam sebagai sumber makanan dan perlindungan. Namun, degradasi vegetasi akibat deforestasi dan alih fungsi lahan telah mendorong harimau keluar dari habitat alaminya, sehingga meningkatkan risiko konflik dengan manusia yang mengancam kelangsungan hidup spesies ini. Penelitian ini bertujuan untuk menganalisis hubungan antara risiko konflik harimau dan kerapatan vegetasi dengan menggunakan Indeks Vegetasi Perbedaan Ternormalisasi (NDVI). Metode yang digunakan menggabungkan pendekatan Participatory Rural Appraisal (PRA) dan analisis spasial berbasis citra satelit (Landsat 8/9 atau Sentinel) untuk menghitung NDVI, sementara data konflik dikumpulkan melalui patroli SMART di 13 desa dan dipetakan menggunakan ArcGIS. Hasil penelitian menunjukkan bahwa risiko konflik harimau Sumatera tersebar secara spasial dengan tingkat variasi yang signifikan di wilayah studi. Risiko tinggi mendominasi dengan persentase 61,5%, yang terutama terkonsentrasi di lima kecamatan: Trumon Tengah, Trumon Timur, Tapak Tuan, Kluet Tengah, dan Meukek. Sementara itu, risiko sedang (23,1%) teridentifikasi di Bakongan Timur dan Trumon Tengah, sedangkan risiko rendah (15,4%) hanya ditemukan di Bakongan Timur. Terdapat pola yang mencolok antara kerapatan vegetasi dan frekuensi konflik, di mana wilayah dengan vegetasi rendah seperti Bakongan Timur (7 kasus) dan Trumon Tengah (6 kasus) mencatat jumlah konflik tertinggi. Sebaliknya, kecamatan dengan tutupan vegetasi tinggi seperti Meukek, Tapaktuan, dan Kluet Tengah masing-masing hanya mencatat satu kasus konflik. Temuan ini secara kuat menunjukkan bahwa degradasi habitat, yang ditunjukkan oleh rendahnya nilai NDVI, merupakan faktor utama yang mendorong meningkatnya interaksi negatif antara harimau dan manusia di wilayah ini.